RENEWABLE ENERGY RESOURCES AND NON-CONVENTIONAL ENERGY SOURCES (American Journal of Pedagogical and Educational Research, 2024)
In this article, information is provided about renewable energy sources, the utilization of solar energy, hydroelectric power sources, wind power plants, and energy derived from seas and oceans. This paper provides a comprehensive overview of innovative approaches for the effective deployment of renewable energy technologies.